Interpreting the results of in situ pull tests on Friction Rock Stabilizers (FRS). Issue 1 (2nd January 2018) - Nicholson, Luke; Hadjigeorgiou, John
Abstract: Friction Rock Stabilizers (FRS) are widely used in underground hard rock mines. An important element of Quality Control and Assurance practice is the use of in situ pull tests. Individual mines undertake in situ pull tests to demonstrate that suitable installation conditions exist for different reinforcement elements, and whether the selected bolts comply with the required standards. This paper reports on a review of 533 pull tests on FRS bolts in six underground hard rock mines in the Sudbury basin. It provides a critical review of factors that influence the performance of FRS bolts. The results are analyzed to provide design values for FRS that can be used as input to deterministic and probabilistic design. The paper concludes with a discussion on the practical implications of the results.